Strategi Pustakawan Membangun Engagement dan Ruang Berkarya Bagi Pemustaka Dalam Medium Digital Pada Layanan Perpustakaan Umum - Irsan (Ikatan Pustakawan Indonesia, 2023)
Librarians are expected to have the will and ability to build engagement with users in digital media. The purpose of this research is to find out the librarian's strategy in building engagement with users in the digital world, especially in encouraging the publication of digital content through services and media owned by public libraries. The research method in this study uses descriptive research using data from books, journals and various websites related to the research topic. The results show that librarians can build engagement with users through digital media so that interactive and productive communication can be established. The involvement of digital library users by engaging in library services will support the digital media ecosystem as a space to work and share knowledge. Meanwhile, increasing digital libraries to expand the social inclusion based library transformation that needs to be developed through the creation of new spaces for millennial users to produce digital content, use social media with e-books, and link literacy products, so as to support empowering knowledge transformation.